2017
DOI: 10.1161/atvbaha.117.309630
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Adiponectin Receptor Regulates Proprotein Convertase Subtilisin/Kexin Type 9 Expression and Inhibits Lesions in ApoE-Deficient Mice

Abstract: Objective— The reduced adiponectin levels are associated with atherosclerosis. Adiponectin exerts its functions by activating adiponectin receptor (AdipoR). Proprotein convertase subtilisin kexin type 9 (PCSK9) degrades LDLR protein (low-density lipoprotein receptor) to increase serum LDL-cholesterol levels. PCSK9 expression can be regulated by PPARγ (peroxisome proliferator–activated receptor γ) or SREBP2 (sterol regulatory element-binding protein 2). The effects of AdipoR agonists on PCSK9 and LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 37 publications
(35 reference statements)
1
37
1
1
Order By: Relevance
“…Elevated PCSK9 is also observed in metabolic syndrome, which affects more than 50% of psoriatic patients [24]. Furthermore, PCSK9 expression can be regulated by agonists adiponectin receptors (AdipoR agonists) through peroxisome proliferator-activated receptor gamma (PPAR-gamma) [32]. Reduction of circulating adiponectin levels and an expression of PPAR-gamma has been proven to be linked with obesity in psoriasis [32,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated PCSK9 is also observed in metabolic syndrome, which affects more than 50% of psoriatic patients [24]. Furthermore, PCSK9 expression can be regulated by agonists adiponectin receptors (AdipoR agonists) through peroxisome proliferator-activated receptor gamma (PPAR-gamma) [32]. Reduction of circulating adiponectin levels and an expression of PPAR-gamma has been proven to be linked with obesity in psoriasis [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PCSK9 expression can be regulated by agonists adiponectin receptors (AdipoR agonists) through peroxisome proliferator-activated receptor gamma (PPAR-gamma) [32]. Reduction of circulating adiponectin levels and an expression of PPAR-gamma has been proven to be linked with obesity in psoriasis [32,33]. According to dual mechanisms in lipids metabolism and inflammation, PCSK9 monoclonal inhibitors termed ewolokumab and alirokumab had proven to be highly promising in bringing added cardiovascular benefit in the ODYSSEY LONG TERM trial and the FOURIER trial [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism underlying the effect of cilostazol on PCSK9 concentrations is poorly understood and could only be speculated. Interestingly, the expression of PCSK9 can be regulated not only by SREBP-2 but also by peroxisome proliferator-activated receptor-γ (PPARγ) [ 27 , 28 ]. Furthermore, activation of the adiponectin receptor can upregulate PCSK9 expression through activation of PPARγ and the adenosine monophosphate-activated protein kinase signaling pathway [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the expression of PCSK9 can be regulated not only by SREBP-2 but also by peroxisome proliferator-activated receptor-γ (PPARγ) [ 27 , 28 ]. Furthermore, activation of the adiponectin receptor can upregulate PCSK9 expression through activation of PPARγ and the adenosine monophosphate-activated protein kinase signaling pathway [ 28 ]. Our previous study revealed that cilostazol could serve as an activator of adenosine monophosphate-activated protein kinase signaling molecules [ 21 ] and adiponectin receptors (unpublished data), and our current study demonstrates that cilostazol treatment can increase plasma adiponectin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that adiponectin and AdipoRon suppress the development of atherosclerotic lesions in apolipoprotein E-deficient (Apoe -/-) mice, an atherogenic mouse model, on a normal or high-fat diet [51][52][53] . Recently, the anti-atherosclerotic effects of osmotin have also been investigated using a variety of animal models in vivo.…”
Section: In Vivo Anti-atherosclerotic Effects Of Osmotinmentioning
confidence: 99%